Desenvolvimento de sistema polimérico para liberação controlada de Alfa-tocoferol - Coelho Junior, Esio de Carvalho (2019)
Oral mucositis is a one of the most debilitating side effects among cancer patients, either induced by radiation or due to chemotherapy. Depending on the severity, the antineoplastic treatment interruption is required until regression of severe oral. Controlled-release delivery system for topical application of antioxidants has been suggested as a promising preventive approach. The present research developed a polymeric system for controlled-release of Alfa-tocopherol through a new encapsulation method. Developed nanomicelles presented mean particle size of 193,80nm (for Alfa- tocopherol concentration of 50mg/ml) and 714,53nm (200mg/ml) (p<0,05); zeta potential was +12,8mV for both concentrations. Alfa-tocopherol entrapped micelles did not present acute nor chronic cytotoxic effects (p>0,05) and presented a higher cell proliferation rate - after evaluation through MTT and clonogenic assays, respectively – over NOE and HNK cells from buccal epithelium. Alfa-tocopherol entrapped micelles exhibited a slower and controlled release pattern when compared to free Alfa- tocopherol. Therefore, this system of controlled release presented a good potential for biologic application, specially 50mg/ml Alfa-tocopherol.